Korelasi Neutrophil to Lymphocyte Ratio (NLR) dengan Derajat Keparahan Pasien COVID-19 di RSUD Undata Palu - Greyta Suangga; Freddy Ciptono (Malahayati Nursing Journal, 2022)
ABSTRACT The world has experienced the COVID-19 pandemic since December 2019 with high morbidity and mortality rate. Patients infected with COVID-19 show varying degrees of severity ranging from asymptomatic, mild, moderate, severe, and critical. Simple laboratory tests such as Neutrophil to Lymphocyte Ratio (NLR) can describe the severity of COVID-19 patients. This study aims to prove the correlation of NLR with the severity of   COVID-19 patients at Undata Palu Hospital. The research method uses analytical surveys with a cross sectional approach and uses secondary data, namely patient medical records from June to December 2021 and included 30 patients. Five patients with mild severity (16.6%), 25 patients with moderate severity (66.7%) and five patients with severe severity (16.7%). The median value for NLR at each level of severity is for mild degrees of 3.8, moderate degrees of 6.1 and severe degrees of 9.2. The results of the study obtained a very strong postitif correlation between NLR values and the severity of COVID-19 infection (r = 0.794) and the average value of NLR is 6.4. The conclusion of this study is that the higher the NLR score, the higher the severity in COVID-19 patients. Keywords: COVID-19, NLR, Patient  ABSTRAK Dunia mengalami pandemik COVID-19 sejak desember 2019 dengan angka morbiditas dan mortalitas yang cukup tinggi. Pasien COVID-19 menunjukan derajat keparahan yang berbeda-beda mulai dari tanpa gejala, ringan, sedang, berat, dan kritis. Pemeriksaan laboratorium yang sederhana seperti Neutrophil to Lymphocyte Ratio (NLR) dapat menggambarkan derajat keparahan pasien COVID-19 . Penelitian ini bertujuan untuk membuktikan korelasi NLR dengan derajat keparahan pasien COVID-19 di RSUD Undata Palu. Metode penelitian menggunakan survei analitik dengan pendekatan cross sectional dan menggunakan data sekunder yaitu rekam medik pasien pada bulan Juni hingga Desember 2021 dengan subyek sebanyak 30 pasien. Pasien yang memiliki derajat keparahan ringan berjumlah lima pasien (16,6%), sedang berjumlah 25 pasien (66,7%) dan berat berjumlah lima pasien (16,7%). Nilai median untuk NLR pada tiap derajat keparahan adalah derajat ringan adalah 3,8, derajat sedang 6,1 dan untuk derajat berat 9,2. Hasil penelitian  didapatkan korelasi positif sangat kuat antara nilai NLR terhadap derajat keparahan infeksi COVID-19 (r=0,794) dengan nilai rata-rata NLR adalah 6,4. Kesimpulan dari penelitian ini adalah semakin tinggi nilai NLR, maka derajat keparahan semakin tinggi pada pasien COVID-19. Kata Kunci: COVID-19, NLR, Pasien